The Ghost of Violence: The Lived Experience of Violence After the Act - Henze-Pedersen, Sofie (Violence against women, 2022)
Based on ethnographic fieldwork and thematic analysis, this article explores how violence is lived after violent events have taken place, and how it shapes women’s everyday lives post-separation. First, the analysis shows how violence is negotiated in the context of a women’s refuge, shaping women’s perceptions of themselves and their experiences. Second, it explores how the potential of violence taking place can influence women’s everyday lives, and third, how past acts of violence can become part of the present atmosphere of everyday life. This raises questions about the meaning of time in analyses of violence.